Global dataset combining open-source hydropower plant and reservoir data - Jignesh Shah; Jing Hu; Oreane Y. Edelenbosch; Michelle T. H. van Vliet (Scientific Data)
Abstract Hydropower is a crucial renewable source that depends heavily on water availability. Analyzing drought and climate change impacts on hydropower potential requires detailed data on both hydropower plant attributes (e.g. plant type and head) and reservoir characteristics (e.g. area, depth and volume). However, existing open-source datasets are poorly integrated: hydropower plant datasets often lack reservoir information, while reservoir datasets commonly miss hydropower plant information. This paper addresses this gap by introducing GloHydroRes, a global dataset that combines existing open-source hydropower plant and reservoir datasets. GloHydroRes includes attributes like plant location, head, plant type as well as reservoir details such as dam and reservoir location, dam height, reservoir depth, area, and volume for 7,775 plants in 128 countries. GloHydroRes covers nearly 79% and 81% of the global installed capacity when compared with installed hydropower data as reported by the EIA(2022) and IRENA (2023), respectively. The open-source GloHydroRes dataset provides crucial data to improve hydropower generation modelling at plant level and can support energy security and planning at continent to global scale.